An exploratory study on the sexual intimacy of male hotel workers and foreign female tourists. (September 2016) - Aslan, Alper
Abstract: Depending on 47 semi-structured interviews conducted with mostly male hotel workers and participant-observation, this qualitative exploratory study examines sexual intimacy between male hotel workers and female tourists within service interactions in apart (apartment) hotels and starred hotels in Marmaris, Turkey. Drawing on practice theory, this study distinguishes between 'playful' and 'non-playful' service interactions. The findings reveal that playful service interactions enable individuals to interact spontaneously within a wide range of behavioral areas, in contrast to scripted interactions. Hence, playful service interactions enable workers and tourists to build sexual intimacy. Management attitudes to sexual intimacy depend on how service intimacy aligns with the hotel's economic interests.